Rancang Bangun Media Pembelajaran Interaktif Menggunakan Adobe Flash CS6 Berbantuan Circuit Verse pada Elemen Penerapan Rangkaian Elektronika - Nurul Hidayah; Yasdinul Huda; Ilmiyati Rahmi Jasril; Hendra Hidayat (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
This study aims to develop interactive learning media for logic gate material in Industrial Electronics Engineering subjects at SMK Negeri 5 Batam by utilizing Adobe Flash CS6 integrated with CircuitVerse. This media is designed to provide a more interesting, interactive, and applicable learning experience, so it is expected to improve students' understanding of the concept of logic gates which is a basic material in the field of electronics. The study uses a Research and Development (R&D) approach with a 4D development model that includes the Define, Design, Develop, and Disseminate stages. Research data were collected through validation by material experts and media experts, as well as practicality tests involving students. Data collection instruments were in the form of validation sheets and student response questionnaires. The validation results showed that the developed learning media obtained a score of 88.20% from material experts and 93.88% from media experts, both of which are in the "very valid" category. The practicality test involving grade XI students obtained a score of 92.80%, indicating that the media is "very practical" to use in the learning process. This interactive media combines elements of text, images, animation, and digital circuit simulations using CircuitVerse, so students can learn logic gate concepts visually and directly practice them virtually. This integration not only makes it easier for students to understand the theory but also trains problem-solving and critical thinking skills. The findings of this study indicate that interactive learning media based on Adobe Flash CS6 and CircuitVerse has great potential to increase learning motivation, student engagement, and conceptual understanding of logic gate material. This media is also relevant to support the implementation of the Independent Curriculum, which emphasizes project-based learning, independent learning, and complete competency mastery.